A Novel Approach for Comparing Selected Metabolites in Citrus Leaves and Fruits Across Datasets - Ryan C. Traband; Xuesong Wang; Mariano Resendiz; Megan Meng; Yoko Hiraoka; Qiong Jia; Rendell Chang; Ethan Eurmsirilerd; Tracy Kahn; Peggy A. Mauk; Amancio De Souza; Anil Bhatia; et al. (Plants)
Citrus fruits are valued not only for their nutritional benefits but also for their rich phytochemical content. Metabolomics has emerged as a comprehensive technique for assessing the chemical composition of fruits. The botanical connection between leaves, flowers, and fruits is reflected in both their structure and chemical composition, particularly in the flow of nutrients between plant organs. We introduced a new logarithm ratio-based approach to compare metabolite profiles between fruits and leaves. We hypothesize that this method allows for the analysis of multiple citrus metabolomic profiles to reveal known and novel correlation patterns, reflecting the dynamic connections between metabolic sources. To test this hypothesis, we leveraged comprehensive leaf metabolomic profiles from over 200 accessions in the Givaudan Citrus Variety Collection and reviewed published metabolomics data for fruits and juices of matching citrus types. By employing logarithm-transformed metabolic ratios within each dataset, we accounted for systematic differences across metabolomic platforms, achieving an unbiased analysis.